Sistem dan Prosedur Pembayaran Gaji dan Upah - Hasan, Hamida (Amsir Management Journal, 2023)
The purpose of this research is to find out the systems and procedures for paying salaries and wages for employees of CV Citra Utama. The method of data analysis used in this study is to use descriptive comparative analysis, namely comparing the systems and procedures for paying salaries and wages applied in companies with systems and procedures for paying salaries and wages based on actual theory with elements of internal control. The results of the study stated that the implementation of systems and procedures for payment of salaries and wages did not reflect the elements of internal control